ИЖТИМОИЙ ГЕОГРАФИК ТАДҚИҚОТЛАРДА АҲОЛИ ТУРМУШ ТАРЗИ КАТЕГОРИЯСИНИ ЎРГАНИШНИНГ БАЪЗИ НАЗАРИЙ МАСАЛАЛАРИ - Облақулов, Ҳ.А. (SCIENCE and SOCIETY, 2024)
In the article, it is shown that the essence and forms of manifestation of the population’s lifestyle, in many cases it is expressed by several aspects, such as their life, work, health and even behavior. The views of foreign and Russian scientists who directly conducted scientific research on the lifestyle of the population, as well as scholars who lived and worked in Central Asia, were analyzed, and the authors’ own opinions were also highlighted on this basis. Also, different aspects and essence of lifestyle and related concepts are explained.